2021
DOI: 10.1111/ejn.15561
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde interference emerges along a gradient as a function of task similarity: A behavioural study

Abstract: Anterograde interference emerges when two opposite (B → A) or identical tasks (A → A) are learned in close temporal succession, suggesting that interference cannot be fully accounted for by competing memories. Informed by neurobiological evidence, this work tested the hypothesis that interference depends upon the degree of overlap between the neural networks involved in the learning of two tasks. In a fully within‐subject and counterbalanced design, participants (n = 24) took part in two learning sessions wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…The motor task to be learned was a gradual visuomotor adaptation protocol. The present apparatus and single‐trial procedures used for every visuomotor adaptation block of the present work are similar to previous work (Hamel, Dallaire‐Jean, et al, 2021; Hamel, de la Fontaine, et al, 2021; Hamel, Lepage, & Bernier, et al, 2021). Briefly, participants performed centre‐out reaching movements towards one of five targets located around a circular array (10 cm radius) from the centre of the virtual environment.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…The motor task to be learned was a gradual visuomotor adaptation protocol. The present apparatus and single‐trial procedures used for every visuomotor adaptation block of the present work are similar to previous work (Hamel, Dallaire‐Jean, et al, 2021; Hamel, de la Fontaine, et al, 2021; Hamel, Lepage, & Bernier, et al, 2021). Briefly, participants performed centre‐out reaching movements towards one of five targets located around a circular array (10 cm radius) from the centre of the virtual environment.…”
Section: Methodsmentioning
confidence: 54%
“…The purpose of the dominant hand acquisition was to induce learning and then manipulate memory consolidation through alcohol ingestion (see Figure 1). The motor task to be learned consisted of compensating for a gradually introduced visual deviation (see Figure 1b), which was to prevent participants from gaining awareness of the deviation, therefore allowing to carry out a fully within‐subject learning design (Hamel, Dallaire‐Jean, et al, 2021; Hamel, de la Fontaine, et al, 2021; Hamel, Lepage, & Bernier, et al, 2021). Using a gradual rather than abrupt deviation was also to minimize the possible anterograde interference with the subsequent learning in the non‐dominant hand session, as adaptation through a gradually introduced sensorimotor perturbation does not transfer between limbs (Hamel, Lepage, & Bernier, et al, 2021; Malfait & Ostry, 2004; Werner et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Relearning paradigms have offered an important approach to studying learning and memory. While many studies have demonstrated savings, indicative of latent retention of information that was acquired in the past, implicit sensorimotor adaptation exhibits attenuation upon re-exposure to a previously learned perturbation (Avraham et al, 2021; Hamel et al, 2022, 2021; Leow et al, 2020; Stark-Inbar et al, 2016; Tsay et al, 2021b; Yin and Wei, 2020). The goal of this paper was to identify the mechanisms underlying this attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, by using methods that isolate the contribution of this recalibration process, we have found that implicit sensorimotor adaptation is actually attenuated during relearning (Avraham et al, 2021; see also Hamel et al, 2022, 2021; Leow et al, 2020; Stark-Inbar et al, 2016; Tsay et al, 2021b; Wang and Ivry, 2023; Yin and Wei, 2020). Savings, when observed in adaptation tasks, appears to largely reflect the operation of other learning processes such as the recall of a successful explicit strategy (Avraham et al, 2021; Haith et al, 2015; Huberdeau et al, 2019; Morehead et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The mechanistic basis for this phenomenon is currently unknown, and may be difficult to determine as the mechanisms underlying anterograde interference are highly complex. For example, a recent study suggests that anterograde interference occurs when overlapping neural networks are utilized in each task learning session, and that the initial learning modifies the properties of its neural networks to constrain further plasticity induction and learning capabilities ( 58 ). Given the documented radiation-induced changes in synaptic function, it is thus possible that exposure further reduces neural network plasticity and anterograde interference avoidance mechanisms.…”
Section: Discussionmentioning
confidence: 99%